Pemberdayaan Ibu Rumah Tangga Berbasis Ekonomi Kreatif melalui Usaha Canang Sari di Desa Ababi Pasca Erupsi Gunung Agung - Tari, Nirmala; Dwiyanti, Ni Made Christine; Majuarsa, I Wayan (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Dhyana Pura – Bali, 2020)
ABSTRAKSalah satu wilayah yang mendapatkan dampak dari Erupsi Gunung Agung adalah Desa Ababi, Kecamatan Abang, Kabupaten Karangasem. Ibu-ibu di daerah ini banyak yang kehilangan pekerjaan kesehariannya. Walaupun terdampak erupsi, ibu-ibu PKK di Abianjero benar-benar tangguh dalam menghadapi tantangan ini. Dalam penerapan Program Kemitraan Masyarakat dengan metode palaksanaan Program Kemitraan Masyarakat dari kegiatan menghasilkan luaran dari mitra adalah: (1) Produksi Canang Sari meningkat; (2) Ekonomi serta jiwa wirausaha masyarakat meningkat. Hasil dari kegiatan Program Kemitraan Masyarakat ini adalah: (1) Pembinaan pengelolaan usaha; (2) Pelatihan pemanfaatan serta penggunaan sarana dan prasarana yang ada untuk memaksimalkan fasilitas yang ada; (3) Pelatihan pada bidang pengolahan produk; (4) Pelaksanaan pelatihan distribusi dan pemasaran; (5) Pelatihan pengelolaan keuangan.Kata kunci : pemberdayaan, ekonomi kreatif, canang sariABSTRACTThe economic restoration after Mount Agung eruption has taken quite a long time, it is also related to the vigilance of the residents and some of the surrounding residents whom each lived outside the village. Meeting the daily needs of the family certainly cannot be delayed. Being the head of the household faces many challenges of daily living. Mount Agung eruption affected the surrounding area. One of the areas that were affected was Ababi Village, Abang District, Karangasem Regency. Many women in the area have lost their daily jobs. Despite the impact of the eruption, PKK women in Abianjero staying resilient in facing this challenges. The implementation of the Community Partnership Program through the method of implementing the Community Partnership Program, the activities resulting: (1) Increase in Canang Sari production; (2) The improvement of community economy and the entrepreneurial spirit. The results of the Community Partnership Program activities are: (1) Guiding business management; (2) Utilization training and the use of existing facilities and infrastructure to maximize existing facilities; (3) Training in the field of product processing; (4) Implementation of distribution and marketing training; (5) Financial management training.Keywords: empowerment, creative economy, canang sari